Kinetics of Amorphous-Crystalline Transformation of Some Se-Te-In Chalcogenide Glasses Using Gao and Wang Model - Balbir Singh Patial; Nagesh Thakur; S.K. Tripathi (Журнал нано- та електронної фізики)
The present study reports the assessment of activation energy for crystallization and crystallization reaction order (Avrami exponent n) for the amorphous-crystallization transformation process of Se85 − xTe15Inx (x  2, 6 and 10) amorphous alloys using differential scanning calorimetry (DSC) technique under non-isothermal conditions at four different heating rates (5, 10, 15 and 20 °C/min) through Gao and Wang model. The introduction of In to the Se-Te system is found to bring a change in crystallization mechanisms and dimensions of growth.